Macroalgal forest restoration: the effect of the foundation species - Bianchelli, Silvia; Fraschetti, Simonetta; Martini, Francesco; Lo Martire, Marco; Nepote, Ettore; Ippoliti, Davide; Rindi, Fabio; Danovaro, Roberto (Frontiers in Marine Science, 2023)
Introduction Active restoration is the strategy needed to trigger or accelerate the recovery of degraded marine habitats, which provide the goods and services essential for preserving biodiversity and human wellbeing. Ecosystem engineers are generally the target species in the ecological restoration of marine ecosystems, and large-sized brown macroalgae (e.g., the Cystoseira complex) are a priority due to their crucial ecological importance and vulnerability in many regions of the Mediterranean Sea. Methods Here, we present the results of a successful intervention of ecological restoration of Gongolaria barbata. Results and Discussion One year after the restoration intervention, we observed the recovery of the canopy in terms of ca. 15m2 with a significant increase in faunal abundance and biodiversity compared with reference areas. However, despite the high restored macroalgal growth rates, the assemblage structure was still significantly different from that of reference pristine areas. Despite the fast faunal colonization of a new 3D habitat linked to the successful re-introduction of the ecosystem engineers (i.e., macroalgae), the complete restoration of the properties of a habitat can be a much longer process. We conclude that, after 1 year, active restoration of macroalgal forests still results in a partial recovery of ecosystem functions (i.e., rehabilitation) rather than a full ecosystem restoration, thus stressing the need for long-term monitoring of restoration interventions.